Experienced Inequality and Preferences for Redistribution - Christopher Roth; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine in how far people's experiences of income inequality affect their preferences for redistribution. We use several large nationally representative datasets to provide evidence that people who have experienced more inequality while growing up are less in favor of redistribution, after controlling for income, demographics, unemployment experiences and current macro-economic conditions. They are also less likely to consider the prevailing distribution of incomes to be unfair, suggesting that inequality experiences affect the reference point about what is a fair division of overall income. Finally, we conduct an experiment to show that individuals randomly exposed to environments promoting inequality in the experience stage of the experiment redistribute less in a subsequent behavioral measure.
Keywords: P16; E60; Z13; 330; inequality; redistribution; macroeconomic experiences; experiment